Bioactive food as dietary interventions for liver and gastrointestinal disease - Watson, Ronald R.; Preedy, Victor R. (Bioactive foods in chronic disease states., 2013)
Bioactive Food as Dietary Interventions for Liver and Gastrointestinal Disease provides valuable insights for those seeking nutritional treatment options for those suffering from liver and/or related gastrointestinal disease including Crohn's, allergies, and colitis among others. Information is presented on a variety of foods including herbs, fruits, soy and olive oil. This book serves as a valuable resource for researchers in nutrition, nephrology, and gastroenterology. Addresses the most positive results from dietary interventions using bioactive foods to impact diseases of the liver and gastrointestinal system, including reduction of inflammation, improved function, and nutritional efficiency. Presents a wide range of liver and gastrointestinal diseases and provides important information for additional research. Associated information can be used to understand other diseases, which share common etiological pathways.